2004
DOI: 10.1063/1.1632997
|View full text |Cite
|
Sign up to set email alerts
|

Europium beta-diketonate temperature sensors: Effects of ligands, matrix, and concentration

Abstract: Europium beta diketonates are easily synthesized highly luminescent complexes with high temperature sensitivity. We report on the temperature dependence of the luminescence of recently synthesized europium complexes originally prepared for use as light emitting diodes. It has been discovered that when incorporated in a polymer matrix, their decay lifetime can provide accurate measurement of temperature. Their lifetime as a function of temperature depends on three factors: (i) the type and number of ligands in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
149
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 17 publications
4
149
0
4
Order By: Relevance
“…Most optical methods for measuring temperature can be grouped into two categories. 51,57,58 The first type of measurements are based on the temperature dependence of the absorption (or the reflection) of certain materials. Examples of this method include thermochromic materials, gas band edge absorptions that shift with temperature, Fabry-Perot interferometers, and changes in refractive indexes.…”
Section: Molecular Thermometersmentioning
confidence: 99%
“…Most optical methods for measuring temperature can be grouped into two categories. 51,57,58 The first type of measurements are based on the temperature dependence of the absorption (or the reflection) of certain materials. Examples of this method include thermochromic materials, gas band edge absorptions that shift with temperature, Fabry-Perot interferometers, and changes in refractive indexes.…”
Section: Molecular Thermometersmentioning
confidence: 99%
“…[7,8] Among the various known probes, Eu(III) chelates, exhibiting sensitized luminescence that can be excited with visible light, are advantageous over UV-excitable probes for the following reasons (among others): i) Long-wave excitation strongly reduces the background fluorescence of biomatter. ii) Visible excitation is less prone to interferences by inner filter effects due to absorption of light.…”
mentioning
confidence: 99%
“…[7] ii) Dinaphthoylmethane (DNM) was reported to efficiently sensitize the luminescence of the Eu(III) ion. iii) The absorption band of DNM extends into the visible part of the spectrum, [14] thus, enabling the use of small and efficient light sources such as LEDs or diode lasers.…”
mentioning
confidence: 99%
“…147 Khalil et al demonstrated the high performance of a Eu(III) complex for a temperature-sensitive paint (temperature sensitivity: 4.42%°C ¹1 ). 148 We had also reported a Tb(III) complex, [Tb(hfa) 3 (H 2 O) 2 ], which is suitable as a temperature-sensing probe since it exhibits effective energy back transfer (BEnT) from the emitting level of the Tb(III) ion to the excited triplet state of the hfa ligand.…”
Section: Thermosensing Propertiesmentioning
confidence: 99%